Solar Radiation Effect on the Complexation Capacity of Aquatic Humic Substances with Metals - Melo, Camila A. [UNESP]; De Toffoli, Ana L. [UNESP]; Moreira, Altair Benedito [UNESP]; Bisinoti, Marcia C. [UNESP] (Soc Brasileira Quimica, 2012)
This study had as main objective to assess the effect of solar radiation on the capacity of the aquatic humic substances (AHS) to complex Al3+, Cr3+, CrO42- and Ni2+. Microcosms were prepared with AHS from Preto River containing 5.0 mg L-1 of dissolved organic carbon and different concentrations of metal species, being exposed to solar radiation, in situ. Conditional stability constants obtained for the AHS-Cr3+, AHS-Ni2+ and AHS-CrO42- complexes were 2.0 x 10(-2), 1.1 x 10(-5) and 2.6 x 10(-2), respectively. The results showed that solar radiation is responsible for decreasing capacity complexation in 15-26% for AHS-Al3+, 15-72% for AHS-Cr3+, 12-18% for AHS-CrO42- and 13-42% for AHS-Ni2+. We can conclude that solar radiation alters metals' availability previously complexed to AHS, making them available in the aquatic body.
Keywords: Aquatic humic substances; metal complexation; solar radiation; Fluorescence